The 1918-19 influenza pandemic in Ireland : a Leinster perspective - Milne, Mary Ida (Trinity College (Dublin, Ireland). Department of History, 2011)
The ‘Spanish’ influenza pandemic killed between 40 and 100 million people during 1918 and 1919, infecting an estimated one fifth or more of the world’s population. It disrupted society and economies, debilitated the armed forces involved in WWl, forced international health authorities to set up influenza monitoring systems and left a lasting legacy of health problems for survivors and of tragic loss and altered family circumstances for the bereaved. In the aftermath of the war, little was done to assess the impact of the influenza on a national or global scale. Since the 1950s, research into the history of the 1918-19 influenza in other countries has burgeoned, coupled with a significant rise in scientific studies enabled by new methods and technologies. As international health authorities continue to advise, in the wake of a limited and perhaps successfully managed pandemic of influenza in 2009, that a new influenza pandemic is imminent, regional and national health authorities use studies and statistics from the 1918-1919 pandemic to model worst-case scenarios for an influenza pandemic in the early twenty-first century, and to create management strategies for future influenza pandemics. On this island, the virus killed a conservative 20,057 people, and infected, this author estimates, perhaps 800,000 people. These figures suggest that the Irish experience of this influenza was proportionately similar to conservative figures for global mortality and morbidity. Its introduction and dispersal was facilitated by the return of soldiers from the arena of war. Although its mortality put it on a par with the well-known nineteenth-century cholera epidemics, it has been generally ignored by Irish historiography until recent years, as historians have been more concerned with political and military issues. This study of the pandemic looks at what happened in Ireland during the pandemic, with a particular focus on the situation in Leinster and the capital city Dublin which, along with Ulster, bore the brunt of the epidemic on the island. However, the patterns of infection and consequently of death varied between the two provinces. Ulster experienced high levels of infection and death during the first waves in the summer and late autumn of 1918, but much lower levels in the third wave in the spring of 1919. Leinster, probably because of the passenger traffic through Dublin port, had high rates of infection and death in all three waves. The study adopts a combination of chronological and thematic approaches. The first chapter reviews international literature on this pandemic of influenza, exploring the chronological development of trends in that literature. The second chapter uses Dublin daily and provincial weekly newspapers to create a chronological survey of how the influenza affected different parts of Leinster. Communities were effectively silenced as it passed through, schools were closed, public events and sporting fixtures cancelled or postponed, shops and businesses closed, court sittings deferred. The third chapter surveys statistics about the pandemic on this island. A thematic approach is taken in the next chapter, which explores government and institutional responses to the crisis. The fifth chapter is both thematic and chronological in approach, looking at the influenza and incarceration over the duration of the epidemic, which also coincided with the term of detention in English and Welsh prisons of those nationalists interned under suspicion of involvement in the so-called ‘German plot’. Influenza became part of the narrative of the nationalist struggle. It forced the Government to release the ‘German plot’ internees. Two of them died from the disease, and Sinn Fein incorporated their deaths into its propaganda. In the sixth chapter, survivors of influenza or people whose families suffered from influenza tell their stories. Collectively, these narratives paint a picture of a time of great fear, of communities silenced by the epidemic as it passed through, and of lives irrevocably altered by the damage the influenza wrought. The seventh chapter looks at influenza from the viewpoint of contemporary medical science and medical doctors, exploring what they used to treat people who had caught the disease, or whose conditions had progressed to pneumonia. The final chapter looks at the epilogue to the epidemic, assessing, as historians of epidemic disease tend to do, what changes it wrought. In the immediate aftermath of the influenza epidemic, the Irish Public Health Council recommended a radical overhaul of the disjointed healthcare system. While its report did not directly refer to the last great disease event faced by the Local Government Board, the recommendations it made had been highlighted by the extra pressure the influenza placed on that system.
Embargo End Date: 2022-01-01
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin, 2011